2022
DOI: 10.1155/2022/2700166
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Axitinib plus Tislelizumab in the Treatment of Advanced Renal Cell Carcinoma

Abstract: Objective. To study and analyze the clinical efficacy of axitinib combined with tislelizumab in the treatment of advanced renal cell carcinoma and its effects on renal function and serum cytokines. Methods. Totally 49 patients with advanced renal cancer treated in our hospital from November 2018 to January 2020 were randomized to treatment with axitinib (control group, n = 27) or axitinib combined with tislelizumab (study group, n = 22). The clinical efficacy, renal function and adverse reactions were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A retrospective study in 2022 showed that Tislelizumab plus Axitinib significantly increased ORR (59.1% vs. 40.7%) and DCR (81.8% vs. 66.7%) in patients with advanced renal clear cell carcinoma compared with acitinib monotherapy. 20 However, there are limited clinical data on the efficacy of Tislelizumab in patients with mccRCC. Further observation and accumulation of more experience are needed to conduct further clinical studies on the efficacy and safety of this combination regimen.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study in 2022 showed that Tislelizumab plus Axitinib significantly increased ORR (59.1% vs. 40.7%) and DCR (81.8% vs. 66.7%) in patients with advanced renal clear cell carcinoma compared with acitinib monotherapy. 20 However, there are limited clinical data on the efficacy of Tislelizumab in patients with mccRCC. Further observation and accumulation of more experience are needed to conduct further clinical studies on the efficacy and safety of this combination regimen.…”
Section: Discussionmentioning
confidence: 99%
“…showed significant differences in the objective response rate (59.1% vs. 40.7%) and disease control rate (81.8% vs. 40.7%) between axitinib combined with tislelizumab and axitinib alone in advanced renal carcinoma. Moreover, the combined treatment group exhibited higher overall survival (median overall survival 8.9 months vs. 5.8 months) ( 35 ). In our case, after diagnosing the patient with TFE3 -rearranged RCC, considering the patient’s young age and presence of metastases, the prognosis was expected to be poor.…”
Section: Discussionmentioning
confidence: 99%